Development of an Attitude Adjustment Crawler Chassis for Combine Harvester and Experiment of Adaptive Leveling System - Jinpeng Hu; Jiahui Pan; Buwang Dai; Xiaoyu Chai; Yixin Sun; Lizhang Xu (Agronomy, 2022)
Body tilt is typically unavoidable for agricultural vehicles or platforms when operated over tough terrain in agricultural production, and, therefore, it is not possible to guarantee the operation performance. Current leveling methods mainly focus on wheeled vehicles or adjustment for single working parts rather than the vehicle body, and few of them could be applied to crawler vehicles. The objective of this research was to put forward an adaptive leveling system for combine harvesters based on the development of a new four-point lifting adjustable crawler chassis. The working principle of the proposed adjustable mechanism was studied on the basis of the analysis of adjustment characteristics under multiple posture adjustment conditions in a RecurDyn environment. The design relies on the combination of the attitude detection of the leveling system and adjustment calculation of driving hydraulic cylinders according to the established mathematical models. Within the designed adjustable extent (including adjustment range of vehicle height 0–87.8 mm, lateral inclination ±3.98° and longitudinal inclination −2.9–5.2°), the leveling performance of lateral and longitudinal inclination was then tested separately. The experiment showed that the leveling system could achieve automatic leveling with an accuracy of ±0.4° and could provide technical support for the development of crawler vehicles.